Upaya Orang Tua Dalam Membimbing Anak Belajar PAI Selama Pembelajaran pada Kelas IV di SDN 12 Limo Suku Sungai Pua - Zulia, Anita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
Islamic education is an educational system that directs and guides in accordance with Islamic ideology. Islamic ideology is based on the guidance of Muslim, namely the Qur’an and Hadist. The limitations of religious knowledge ang the use of technology are one of the obstacles for parents, especially in online learning, parents are required to guide their children in internet based learning. The purpose of this research to find out how parents are traying to guide their children to learn PAI during online learning. This study uses descritive qualitative research by describing the phenomena that occur in the field. To obtain data in this study through observation, interviews and documentation. The results of this study indiciate that the efforts of parents in guiding children to learn PAI during online learning at SDN 12 Limo Suku Sungai Pua tribe are to increase children’s motivation in learning, overcome learning difficulties and help overcome them, provide guidance while studying, provide facilities and means to support learning and supervise and manage children’s learning time.